To substitute, we fist need one variable in terms of the other (plus a constant). Rearrange the first equation to get y in terms of x:
-x + y = 9
y = 9 + x
Substitute this value of y into the second equation:
x - y = -9
x - (9+x) = -9
x - 9 - x = -9
-9 = -9
This is true, for all values of (x,y) satisfying y = 9+x. So there are infinite solutions to this system of equations.
You can see this if you graph the lines - they're identical, i..e they perfectly overlap. So any point on the line is a solution to both equations = infinite solutions.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?